Forecast of Potential Areas of Urban Expansion in the Laguna de Bay Basin and Its Implications to Water Supply Security - Tanganco, Lexxel JJ U (Archīum Ateneo, 2019)
The Laguna de Bay Basin is a highly important economic and environmental resource with a variety of land and water uses. This study investigates the status and trends of the land cover change of the Laguna de Bay Basin, focusing on urban expansion. Using the Land Transformation Model (LTM), drivers of conversion of agricultural and natural land cover to built-up land were determined based on the land cover change between 2003 and 2015. Drivers identified include distance to rivers, distance to roads, distance to Laguna Lake, distance to existing built-up, slope, population density, soil type, temperature, and rainfall. A forecast of urban expansion assuming “business-as-usual” conditions to year 2050 shows the expansion of built-up areas southward of the National Capital Region towards the areas of Cavite, Batangas, and Laguna, and eastward to Rizal. This poses a risk to the water bodies near these areas. Potential implications on water quality and quantity, as components of overall water supply security, are discussed. A framework for future research integrating land use and land cover change (LULCC) and water supply security is proposed. The study recommends the continued implementation of integrated watershed management and the development of more transboundary management policies.